The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fnhum.2014.00428
|View full text |Cite
|
Sign up to set email alerts
|

A model-based analysis of impulsivity using a slot-machine gambling paradigm

Abstract: Impulsivity plays a key role in decision-making under uncertainty. It is a significant contributor to problem and pathological gambling (PG). Standard assessments of impulsivity by questionnaires, however, have various limitations, partly because impulsivity is a broad, multi-faceted concept. What remains unclear is which of these facets contribute to shaping gambling behavior. In the present study, we investigated impulsivity as expressed in a gambling setting by applying computational modeling to data from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 66 publications
(97 reference statements)
2
36
0
Order By: Relevance
“…By allowing participants to vary their bet size, switch between slot machines and place double-or-nothing bets, we could estimate how participants not only inferred the trial-by-trial probability of winning, but also updated higherorder beliefs about the fluctuations (volatility) of a slot machine's winning probability. Similar to the rationale outlined in prior work, (Paliwal et al, 2014) we believe that a naturalistic paradigm engenders increased behavioural engagement, allowing us to quantify behaviour that has a higher fidelity to 'real world' impulsivity. Additionally, model-based estimates derived from the computational framework may afford us an individual profile of how each participant represented (and responded to) environmental uncertainty.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…By allowing participants to vary their bet size, switch between slot machines and place double-or-nothing bets, we could estimate how participants not only inferred the trial-by-trial probability of winning, but also updated higherorder beliefs about the fluctuations (volatility) of a slot machine's winning probability. Similar to the rationale outlined in prior work, (Paliwal et al, 2014) we believe that a naturalistic paradigm engenders increased behavioural engagement, allowing us to quantify behaviour that has a higher fidelity to 'real world' impulsivity. Additionally, model-based estimates derived from the computational framework may afford us an individual profile of how each participant represented (and responded to) environmental uncertainty.…”
Section: Introductionmentioning
confidence: 84%
“…In prior work, we found that participant-specific parameter estimates encoding different aspects of uncertainty (such as an estimate of environmental uncertainty, the tonic volatility ) related to a clinical measure of impulsivity in a cohort of healthy individuals (Paliwal et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations